Regenerative medicine technologies applied to transplant medicine. An update - Petrosyan, Astgik; Montali, Filippo; Peloso, Andrea; Citro, Antonio; Byers, Lori N.; La Pointe, Catherine; Suleiman, Mara; Marchetti, Alice; Mcneill, Eoin P.; Speer, Allison L; Ng, Wai Hoe; Ren, Xi; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Regenerative medicine (RM) is changing how we think and practice transplant medicine. In regenerative medicine, the aim is to develop and employ methods to regenerate, restore or replace damaged/diseased tissues or organs. Regenerative medicine investigates using tools such as novel technologies or techniques, extracellular vesicles, cell-based therapies, and tissue-engineered constructs to design effective patient-specific treatments. This review illustrates current advancements in regenerative medicine that may pertain to transplant medicine. We highlight progress made and various tools designed and employed specifically for each tissue or organ, such as the kidney, heart, liver, lung, vasculature, gastrointestinal tract, and pancreas. By combing both fields of transplant and regenerative medicine, we can harbor a successful collaboration that would be beneficial and efficacious for the repair and design of de novo engineered whole organs for transplantations.